(untitled) (Texas Journal of Medical Science, 2023)
Some eye diseases like cataract, glaucoma, diabetic retinopathy, and age-related macular degeneration were reported to have potential relation to obesity. Obesity possesses an increased risk for both elevated intraocular pressure and systemic vascular abnormalities such as hypertension and arteriosclerosis.